e-NURSE - aplicativo móvel para o ensino da avaliação e diagnósticos de enfermagem - Camila Santana Domingos (2024)
Introduction: The incorporation of the Nursing Process in education must be transversal, and curricula should consider the student as the protagonist, providing opportunities for critical thinking and clinical reasoning. Additionally, we must consider the current transition from the analog model of education to the digital one. Objective: To develop a mobile application for teaching nursing assessment and Nursing Diagnoses in the care of clinical patients. Method: This methodological study with technological production was conducted in five stages. The first stage was the definition of content. The theoretical framework used for nursing assessment was the Theory of Basic Human Needs. For the nursing diagnoses stage, the International Classification for Nursing Practice and NANDA-International were used. The pedagogical approach adopted was constructivism. Five clinical cases were used as learning resources. The databases from the software Information System with the Nursing Process in Intensive Care and Information System with the Nursing Process in Medical and Surgical Clinical Units supported the content included in the app for teaching the Nursing Process. In the second stage, diagnostic link validation was carried out using the Delphi technique in two rounds. The Content Validity Index was used to evaluate the degree of agreement among experts. In the third stage, the app was programmed and designed using the Android Studio® development interface and Java® language. The fourth stage involved testing to identify flaws and make improvements. The fifth stage consisted of an evaluation of the app by nursing students using the user version of the Mobile App Rating Scale (uMARS). Data were analyzed using the Statistical Package for Social Science® program, version 23.0. Descriptive and correlation analyses were performed. This research was approved by the Human Research Ethics Committee of the Federal University of Minas Gerais (Opinion No. 5.596.632). Results: The mobile app developed was named e-Nurse. Its content contains 128 empirical indicators grouped into 34 Basic Human Needs. The e-Nurse includes 60 Nursing Diagnosis labels, and in the validation process of the indicators with Nursing Diagnoses, they achieved a minimum content validity index of 80%. The programming involved creating screens with theoretical and practical concepts. The testing stage involved nine participants for the improvement of the mobile app. In the fifth stage, 23 nursing students evaluated the app using uMARS. The app received an average objective quality score of 4.4 (SD: 0.2; 95% CI: 3.8-4.9) and a subjective score of 4.0 (SD: 0.4; 95% CI: 3.0-4.7). The e-Nurse was classified as a high-quality app (> 4 points). Conclusion: The e-Nurse app is an accessible and user-friendly technological innovation that allows students to perform nursing assessments and establish nursing diagnoses, while simultaneously testing the clinical reasoning utilized.